Spectral Characterization, Antioxidant, Cytotoxic and Molecular Docking Studies of Nanosized Cu(II) Hybrid with 2-Hydroxyphenylethylideneamino)quinolin-2(1H)-one - M. Anazy, Murefah; S. Alturiqi, Amani; S. Al-Farraj, Eida; A. Ammar, Reda (Asian Journal of Chemistry, 2020)
Nanosized Cu(II) hybrids derived 2-hydroxyphenylethylideneamino)quinolin-2(1H)-one (HPEAQ) was synthesized and characterized by spectroscopic and TGA analysis. The IR, 1H & 13C NMR spectra revealed that the HPEAQ coordinated its CH=N, C=O and deprotonated hydroxyl groups in coordination with Cu(II) ions (1-4). The geometries of copper(II) hybrids are octahedral geometry. The XRD and SEM images unequivocally definite the nanosized copper chelate (2). The antioxidant, cytotoxic activities and molecular docking technique of the compounds have also been screened.